Inhibition kinetics of digestive proteases for Anticarsia gemmatalis - PATARROYO-VARGAS, ADRIANA M.; CORDEIRO, GLÁUCIA; SILVA, CAROLINA R. DA; SILVA, CAMILA R. DA; MENDONÇA, EDUARDO G.; VISÔTTO, LILIANE E.; ZANUNCIO, JOSÉ C.; CAMPOS, WELLIGTON G.; OLIVEIRA, MARIA GORETI A. (Anais da Academia Brasileira de Ciências, 2020)
Anticarsia gemmatalis Hübner, 1818 (Lepidoptera) is a major pest of soybean in the Brazil. It is known that the reduction of proteolytic activity by the ingestion of protease inhibitors reduces digestion and larval development of the insects. Control via inhibition of the digestive enzymes necessitates deeper knowledge of the enzyme kinetics and the characterization of the inhibition kinetics of these proteases, for better understanding of the active centers and action mechanisms of this enzyme. Trypsin-like proteases found in the gut of Anticarsia gemmatalis were purified in a p-aminobenzamidine agarose column. Kinetic characterization showed KM 0.503 mM for the L-BApNA substrate; Vmax= 46.650 nM s-1; Vmax/[E]= 9.256 nM s-1 mg L-1 and Vmax/[E]/KM= 18.402 nM s-1 mg L-1 mM. The Ki values for the inhibitors benzamidine, berenil, SKTI and SBBI were 11.2 µM, 32.4 µM, 0.25 nM and 1.4 nM, respectively, and all revealed linear competitive inhibition. The SKTI showed the greatest inhibition, which makes it a promising subject for future research to manufacture peptide mimetic inhibitors.Anticarsia gemmatalis Hübner, 1818 (Lepidoptera) is a major pest of soybean in the Brazil. It is known that the reduction of proteolytic activity by the ingestion of protease inhibitors reduces digestion and larval development of the insects. Control via inhibition of the digestive enzymes necessitates deeper knowledge of the enzyme kinetics and the characterization of the inhibition kinetics of these proteases, for better understanding of the active centers and action mechanisms of this enzyme. Trypsin-like proteases found in the gut of Anticarsia gemmatalis were purified in a p-aminobenzamidine agarose column. Kinetic characterization showed KM 0.503 mM for the L-BApNA substrate; Vmax= 46.650 nM s-1; Vmax/[E]= 9.256 nM s-1 mg L-1 and Vmax/[E]/KM= 18.402 nM s-1 mg L-1 mM. The Ki values for the inhibitors benzamidine, berenil, SKTI and SBBI were 11.2 µM, 32.4 µM, 0.25 nM and 1.4 nM, respectively, and all revealed linear competitive inhibition. The SKTI showed the greatest inhibition, which makes it a promising subject for future research to manufacture peptide mimetic inhibitors.